Biogeochemical characterization of a LNAPL body in support of STELA - Irianni Renno, Maria, author; De Long, Susan K., advisor; Sale, Thomas C., advisor; Borch, Thomas, committee member; Payne, Fred, committee member (Colorado State University. Libraries, 2013)
Microbially-mediated depletion of light non-aqueous phase liquids (LNAPL) has gained regulatory acceptance as a method for managing impacted sites. However, the fundamental microbiology of anaerobic hydrocarbon degradation, in source zones, remains poorly understood. Two site-specific studies (Zeman, 2012 & McCoy, 2012) performed at the Center for Contaminant Hydrology (CCH), Colorado State University (CSU) demonstrated that LNAPL biodegradation increases drastically when temperatures are maintained between 18°C and 30°C as compared to lower or higher temperatures. These results have supported the design of a Sustainable Thermally Enhanced LNAPL Attenuation (STELA) technology that is currently being tested at field scale at a former refinery in Wyoming. The focus of the present study was to perform a depth-resolved characterization of the mixed microbial communities present in LNAPL-impacted soils, as well as to characterize the site's geochemical parameters in order to establish a baseline data set to evaluate the STELA system performance. Seventeen soil cores were collected from the impacted site, frozen on dry ice and subsampled at 6-inch intervals for analysis of biogeochemical parameters. Multi-level sampling systems were installed at the core sites to monitor aqueous and gas phases. Diesel and gasoline range organics and benzene, toluene, ethylbenzene and xylenes (BTEX) present in the cores and in water samples were analyzed. Temperature, inorganic dissolved ions, pH, and oxidation reduction potential (ORP) were also measured. DNA was extracted in triplicate from each subsample corresponding to the study's center core (21 samples). Total Eubacteria and Archaea were quantified via 16S rRNA gene-targeted qPCR. Microorganisms present at selected depth intervals were identified via 454 pyrosequencing of both eubacterial and archaeal 16S rRNA genes. Results indicate that at the study site, the majority of the hydrocarbon contamination is found between 5 and 12 feet below ground surface (bgs). The average of the maximum total petroleum hydrocarbon (TPH) soil concentrations within each core was 17,800 mg/kg with a standard deviation of 8,280 mg/kg. The presence of methane in the vadose zone and depleted sulfate concentrations in water samples suggest that both methanogenesis and sulfate reduction are likely driving LNAPL depletion processes. Four distinct biogeochemical zones where identified within the surveyed aquifer region. Interestingly, the quantity of eubacterial 16S rRNA genes dominate the quantity of archaeal 16S rRNA genes at sampled depths within the aerobic aquifer region. In the strictly anaerobic aquifer regions, these quantities are approximately equal. The latter can be interpreted as evidence of syntrophism, which has been reported in other hydrocarbon biodegradation studies. Pyrosequencing results support these findings as well and contribute to further elucidating the spatial correlation between microbial communities and geochemical parameters. In-situ biodegradation rates are largely controlled by the quantity and activity of key microbes capable of mediating conversion of specific hydrocarbon constituents. Furthermore, it is anticipated that biodegradation rates are governed by complex interactions of diverse microbial communities that vary both in space and time. The overall vision of this initiative is that advancing a better understanding of processes controlling biologically mediated losses of LNAPL will support the development of more efficient treatment technologies for LNAPL releases. In particular, the site specific analysis produced through this study will support the development of STELA.
Keywords: benzene; biogeochemistry; bioremediation; LNAPL; microbial ecology; petroleum